FNDC5/irisin is expressed and regulated differently in human periodontal ligament cells, dental pulp stem cells and osteoblasts. (April 2021) - Yang, Yang; Pullisaar, Helen; Landin, Maria A.; Heyward, Catherine Anne; Schröder, Maria; Geng, Tianxiang; Grano, Maria; Reseland, Janne Elin
Highlights: FNDC5/irisin is expressed in hPDL cells, hDPCs, hOBs, rodent periodontium and pulp. FNDC5/irisin expression is differently regulated in hPDL cells, hDPCs, and hOBs. Odontoblast-like differentiation may affect FNDC5/irisin expression and secretion. Abstract: Objective: To examine the expression and regulation of fibronectin type III domain-containing protein 5/irisin (FNDC5/irisin) in primary human periodontal ligament (hPDL) cells, dental pulp stem cells (hDPCs) and osteoblasts (hOBs). Methods: FNDC5/irisin was identified in sections of paraffin embedded rat maxillae, cryo-sections of 3D cultured spheroids hPDL cells, hDPCs and hOBs, 2D cultured hPDL cells, hDPCs and hOBs by immunohistochemistry. The expression of FNDC5/irisin was identified by qPCR, followed by sequencing of the qPCR product. Regulation of FNDC5/irisin expression in hPDL cells, hDPCs and hOBs were evaluated after administration of different concentrations of irisin and all-trans retinoic acid (ATRA). qPCR and ELISA were used to identify expression and secretion of FNDC5/irisin in odontoblast-like differentiation of hDPCs. Results: FNDC5/irisin was confirmed to be present in rat periodontium and dental pulp regions, as well as in 2D and 3D cultured hPDL cells, hDPCs and hOBs. BLAST analyses verified the generated nucleotide alignments matched human FNDC5/irisin. FNDC5/irisin gene expression was enhanced during odontoblast-like differentiation of hDPCs whereas the secretion of the protein was decreased compared to control. The protein signals in rat periodontal and pulpal tissues were higher than that of alveolar bone, and the expression of FNDC5/irisin was differently regulated by recombinant irisin and ATRA in hPDL cells and hDPCs compared to hOBs. Conclusions: FNDC5/irisin expression was verified in rodent periodontium and dental pulp, and in hPDL cells, hDPCs and hOBs. The FNDC5/irisin expression was regulated by recombinant irisin and ATRA. Finally, expression and secretion of FNDC5/irisin were affected during odontoblast-like differentiation of hDPCs.